1994
DOI: 10.1007/bf00220797
|View full text |Cite
|
Sign up to set email alerts
|

Recombination of Solanum brevidens chromosomes in the second backcross generation from a somatic hybrid with S. tuberosum

Abstract: Solanum brevidens synteny groups were examined with 47 widely-distributed RFLP markers in 17 BC2 progeny from six fertile BC1 plants. The BC1 plants were derived from a single S. brevidens + S. tuberosum somatic hybrid backcrossed with S. tuberosum (potato). Probes which were linked in potato and tomato were also found to be syntenic along each of the 12 S. brevidens chromosomes. More than half of the S. brevidens synteny groups had lost one or more S. brevidens-specific RFLPs in the BC2, suggesting that recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

1995
1995
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 16 publications
0
19
0
1
Order By: Relevance
“…For RAPD analysis, DNA was extracted from single leaves of material grown in vitro, using the microprep method described by McGrath et al (1994). A miniprep DNA extraction protocol was used when larger quantities of DNA were required for RFLP analysis (Fulton et al 1995).…”
Section: Dna Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…For RAPD analysis, DNA was extracted from single leaves of material grown in vitro, using the microprep method described by McGrath et al (1994). A miniprep DNA extraction protocol was used when larger quantities of DNA were required for RFLP analysis (Fulton et al 1995).…”
Section: Dna Extractionmentioning
confidence: 99%
“…Somatic hybrids between S. brevidens and S. tuberosum have provided a new source of resistance to Potato Leaf Roll Virus and Erwinia soft rots (Helgeson et al 1986;Austin et al 1988). Resistance to Potato Virus Y (PVY) can be obtained from somatic hybrids of potato and S. etuberosum (Novy and Helgeson 1994). S. commersonii and potato have been hybridized to give a new resistance to bacterial wilt disease caused by Ralstonia solanacearum (Laferriere et al 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result suggests that another potato chromosome, in addition to chromosome 8, is in aneuploidic state (five copies). Previous RFLP marker analysis indicated that C75-5 may contain parts of chromosomes 2, 4 and 5 from S. brevidens (McGrath et al 1994(McGrath et al , 1996. However, our GISH analysis only revealed the chromosome 8 from S. brevidens.…”
Section: Resultsmentioning
confidence: 97%
“…Molecular marker analysis indicated that the BC 2 clone C75-5 may retain a complete chromosome 8 and part of chromosomes 2, 4 and 5 from S. brevidens (McGrath et al 1994(McGrath et al , 1996. We used RFLP analysis to test if chromosome 8 of S. brevidens in C75-5 has been transmitted into C75-5+297.…”
Section: Resultsmentioning
confidence: 97%